Report of a case of paroxysmal nocturnal hemoglobinuria (PNH) with complex evolution and liver transplant - Railene Célia B. Alencar; Andréa M. Guimarães; Lacy C. Brito Junior
ABSTRACT The paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired disease, with thrombotic episodes and frequent pancytopenia. We report the case of a 32 year-old female PNH patient with bone marrow aplasia, which followed a complex course, diagnosed with aplastic anemia associated with PNH, evolving in three years with Budd-Chiari syndrome and liver transplantation. Post-transplant complications, hepatic arterial thrombosis, graft rejection, liver retransplantation and treatment of PNH with eculizumab. Clinical stabilization and cessation of symptoms were achieved.